Pulp and Paper Mill References - Holmberg, Robert G. (Friends of the Athabasca Environmental Association, 1989)
This is an annotated list of books and other materials related to the development and operation of pulp and paper mills in the Athabasca River basin. The purpose of the list is to encourage members of the public to learn about these industries so that they can ask informed questions, and better understand the answers given, at Environmental Impact Assessments (BIAs) and other meetings that will be held when new or expanded mills are proposed. The materials are grouped into various categories including: Air Pollution, Chemistry, Economics, Environmental Impact Assessments, Forestry, Human Health, Legal, Logging, Monitoring, Planning, Pulp and Paper Mills, Water Pollution, Water: Rivers and Lakes, Waste Management.